Spatial behavior of the Dar-Zarrouk parameters for exploration and differentiation of water bodies aquifers in parts of Konkan coast of Maharashtra, India - Naidu, Suneetha; Gupta, Gautam; Shailaja, G.; Khan, Tahama (My University, 2021)
Demarcation of aquifer boundaries and hydro-geologic characterization can help in proper management and conservation of groundwater resources of a coastal region. The objective of the present study is to identify and delineate the groundwater-bearing zones and protection of freshwater aquifers from saltwater ingress in the northern parts of Sindhudurg district, western Maharashtra, India. A total of 86 vertical electrical soundings (VES) were carried out by Schlumberger electrode arrangement to infer the sub-surface lithology around Kankavali, Vijaydurg, and Malvan. The Dar-Zarrouk parameters were computed to generate the spatial variation maps of transverse resistance (T), longitudinal conductance (S), transverse resistivity (ρt), and longitudinal resistivity (ρl), to decipher the resistivity contrast of fresh water and salt water-bearing formations. The results demonstrate that these parameters provide a better resolution in delineating the seawater intrusion in coastal aquifers. The overburden aquifer protective capacity computed from the longitudinal conductance suggests that 59% of the area has poor aquifer protection, while 23% has weak, 11% has moderate and 7% falls in good protective capacity rating. This parameter reveals the infiltration of contaminants and the health of the aquifer. The electrical anisotropy (λ) value ranges from 0.9 to 5.1, suggesting an increase from SW to NE and also from SE to NW. The fracture porosity (φf) ranges from 10−6 to 0.65, which corroborates with the high and low λ values, reflecting that fracturing is due to anisotropy and significant reserves of groundwater could be exploited in this coastal region.
Keywords: Seawater intrusion; Vertical electrical sounding; Aquifer; Dar-Zarrouk parameters; Sindhudurg; India